THE UTILIZATION OF VRIO ANALYSIS TO MEASURE SUSTAINABLE COMPETITIVE ADVANTAGE AT BANK BTN COMPONENTS - Tonny Sudjatnika; Hedwigis Esti Riwayati (Yayasan Education and Social Center, 2023)
This research aimed to analyze Bank BTN's internal resources based on the conceptual framework of Valuables, Rareness, and Inimitable, and Organized by the framework of grounded theory and the Gioia method. The Primary data was obtained from internal Bank BTN as the unit of analysis. Data was sourced from the interview results with informants chosen by researchers. In addition to primary data, this study also combined secondary data sourced from company documents and reports. The categorical analysis uses to parse interview data and find internal resources which spotted Bank BTN's competitive advantage. This research has discovered four dimensions of a company's competitive advantage: strategic financial capital, strategic human resources capability, strategic business innovation, and business sustainability. The majority of categories still classify as a temporary competitive advantage